Cinematic features in poetry of Jassim Mohamed Jassim - Jameel Moosa, Sulaf (Journal of College of Education, 2019)
The concepts of the image, the shot, the angle of view, the motion of the camera, and other cinematic terms of cinema art. However, in the modern era, poetry may draw many other techniques and concepts of art, a clear reference to the phenomenon of overlapping arts, which has become a phenomenon of renewal at the level of all arts.In this research we will discuss the poetry of Jassim Mohammed Jassim from the point of view of its relationship with cinema art. As the poet excelled in the ability to employ concepts and cinematic mechanisms in his poetry in such a way that makes it a phenomenon worthy of reflection and study. Therefore, we will stand at the concept of the image and the concept of the shot long and short, as well as tracking the movement of the camera and the point of photography in his poetic speech, which suggests a fine overlap between the art of cinema and poetry. Thus, this discourse suggests that the poet has benefited from the art of cinema in the formulation of its poems. These poems often pass through the eyes of the recipient as if they were an integrated film.